การพัฒนาหุ่นยนต์เดลต้าแบบสามองศาอิสระ - นภสร โกวรรธนะกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purpose of thesis is to study and develop a parallel delta robot with three pure translation degrees of freedom. The robot is designed to be a research robot that works with human and controlled by open architecture controller. The Robot requires installation space 65x65x80 cm3 while its workspace is 30x35x37.5 cm3. This robot is driven by three 6 W permanent magnet DC motor, which their power consumption is quite low, and sensed its end point position by three 2500 ppr incremental encoders. The resulting accuracy, repeatability and resolution are 8.1, 0.5 and 0.04 mm. respectively. The servoing rate of the controller and amplifier is up to 10 kHz. Furthermore, the robot has been tested with various equipments including manual pulse generator and digital camera. In the thesis, the robot has demonstrated that it can control position of its end effector to be on the targets that are defined by shape, size and color.